Convergent behavior of extended stalk regions from staphylococcal surface proteins with widely divergent sequence patterns - Yarawsky, Alexander E; Ori, Andrea L; English, Lance R; Whitten, Steven T; Herr, Andrew B (bioRxiv, 2023)
and are highly problematic bacteria in hospital settings. This stems, at least in part, from strong abilities to form biofilms on abiotic or biotic surfaces. Biofilms are well-organized multicellular aggregates of bacteria, which, when formed on indwelling medical devices, lead to infections that are difficult to treat. Cell wall-anchored (CWA) proteins are known to be important players in biofilm formation and infection. Many of these proteins have putative stalk-like regions or regions of low complexity near the cell wall-anchoring motif. Recent work demonstrated the strong propensity of the stalk region of the accumulation-associated protein (Aap) to remain highly extended under solution conditions that typically induce compaction or other significant conformational changes. This behavior is consistent with the expected function of a stalk-like region that is covalently attached to the cell wall peptidoglycan and projects the adhesive domains of Aap away from the cell surface. In this study, we evaluate whether the ability to resist compaction is a common theme among stalk regions from various staphylococcal CWA proteins. Circular dichroism spectroscopy was used to examine secondary structure changes as a function of temperature and cosolvents along with sedimentation velocity analytical ultracentrifugation and SAXS to characterize structural characteristics in solution. All stalk regions tested are intrinsically disordered, lacking secondary structure beyond random coil and polyproline type II helix, and they all sample highly extended conformations. Remarkably, the Ser-Asp dipeptide repeat region of SdrC exhibited nearly identical behavior in solution when compared to the Aap Pro/Gly-rich region, despite highly divergent sequence patterns, indicating conservation of function by various distinct staphylococcal CWA protein stalk regions.